A randomized controlled trial of granulocyte colony-stimulating factor for the treatment of severe sepsis due to melioidosis in Thailand. - Cheng, A; Limmathurotsakul, D; Chierakul, W; Getchalarat, N; Wuthiekanun, V; Stephens, D; Day, N; White, N; Chaowagul, W; Currie, B; Peacock, S (2007)
BACKGROUND: Melioidosis is a tropical infectious disease associated with significant mortality. Most deaths occur early and are caused by fulminant sepsis. METHODS: In this randomized, placebo-controlled trial, we assessed the efficacy of lenograstim (granulocyte colony-stimulating factor [G-CSF], 263 mu g per day administered intravenously) in ceftazidime-treated patients with severe sepsis caused by suspected melioidosis in Thailand. RESULTS: Over a 27-month period, 60 patients were enrolled to receive either G-CSF (30 patients, 18 of whom had culture-confirmed melioidosis) or placebo (30 patients, 23 of whom had culture-confirmed melioidosis). Mortality rates were similar in both groups (G-CSF group, 70%; placebo group, 87%; risk ratio, 0.81; 95% confidence interval, 0.61-1.06; P=.2), including among patients with confirmed melioidosis (83% vs. 96%; P=.3). The duration of survival was longer for patients who received G-CSF than for patients who received placebo (33 h vs. 18.6 h; hazard ratio, 0.56; 95% confidence interval, 0.31-1.00; P=.05). CONCLUSIONS: Receipt of G-CSF is associated with a longer duration of survival but is not associated with a mortality benefit in patients with severe sepsis who are suspected of having melioidosis in Thailand. We hypothesize that G-CSF may "buy time" for severely septic patients, but survival is more likely to be improved by management of associated metabolic abnormalities and organ dysfunction associated with severe sepsis.